Español - Mena Jimenez, Freddy Mauricio (2022)
Introduction: Polycystic ovary syndrome (PCOS) is an endocrine-metabolic disorder of great importance because it affects the quality of life of those women who suffer from it. The pathogenesis of insulin resistance and vitamin D insufficiency are associated with a predisposition to PCOS, which is considered one of the most frequent endocrine disorders in women worldwide, with a prevalence of 5-15%. Methods: The present investigation is of a narrative or non-systematic type in which a rigorous search was carried out in different databases such as: Science Direct, Redalyc, PubMed, Scielo, UpToDate, Google Scholar, etc. and Spanish. Discussion: 73% of women with PCOS manifest vitamin D deficiency which is related to insulin resistance since 50% of women with PCOS present hyperinsulinemia and insulin resistance with alterations in carbohydrate metabolism and increased fasting glucose. Together, vitamin D deficiency and insulin resistance can cause infertility, hirsutism, preterm delivery, gestational bacterial vaginosis, gestational diabetes, and early menopause. Conclusions: The supplementation and treatment with vitamin D in PCOS could have a beneficial effect on the different metabolic alterations and that improves insulin sensitivity, testosterone levels, ovulation parameters and ovarian folliculogenesis.